2018
DOI: 10.3389/fendo.2018.00758
|View full text |Cite
|
Sign up to set email alerts
|

Chemoresistance: Intricate Interplay Between Breast Tumor Cells and Adipocytes in the Tumor Microenvironment

Abstract: Excess adipose tissue is a hallmark of an overweight and/or obese state as well as a primary risk factor for breast cancer development and progression. In an overweight/obese state adipose tissue becomes dysfunctional due to rapid hypertrophy, hyperplasia, and immune cell infiltration which is associated with sustained low-grade inflammation originating from dysfunctional adipokine synthesis. Evidence also supports the role of excess adipose tissue (overweight/obesity) as a casual factor for the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 213 publications
(253 reference statements)
0
36
0
Order By: Relevance
“…Finally, obese breast cancer patients have been shown to be more resistant to chemotherapy, the main standard of care of metastatic breast cancer. Obesity has been shown to contribute to chemoresistance by altering drug pharmacokinetics, inducing chronic inflammation, as well as altering tumor-associated adipocyte adipokine secretion 32 . The role of obesity-driven ECM production in chemoresistance remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, obese breast cancer patients have been shown to be more resistant to chemotherapy, the main standard of care of metastatic breast cancer. Obesity has been shown to contribute to chemoresistance by altering drug pharmacokinetics, inducing chronic inflammation, as well as altering tumor-associated adipocyte adipokine secretion 32 . The role of obesity-driven ECM production in chemoresistance remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The role of FAs in cancer progression and treatment resistance implicates various physiological functions of FAs in relation to both dietary intake and de novo synthesized FAs. It is proposed to be achieved by (i) alterations in cell membrane composition, (ii) the biosynthesis of lipid-signaling molecules, and (iii) its role in metabolic reprogramming as an energy source [reviewed in (9,10)]. Both SFAs and MUFAs are implicated in alterations within cancer cell membrane composition known as membrane lipid saturation.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Bcl-2 shows as well anti-autophagic activity by stabilizing lysosomal membrane and preventing lysosomal destabilization [100,101]. As a result, cancer cells, that express elevated Bcl-2 levels, are more chemoresistant to the standard treatments that activate either apoptosis or autophagic cell death [102,103]. Not surprisingly, we found that HepG2 cells upon NP treatment did not exhibit lysosomal dysfunction (Figure 5g) and destabilization (Figure 5f and Supplementary Figure S6).…”
Section: P53 Sub-cellular Localization Mediates Hepatic Cell Responsementioning
confidence: 77%